Carbon farming via assisted natural regeneration as a cost-effective mechanism for restoring biodiversity in agricultural landscapes. Issue 50 (June 2015) - Evans, Megan C.; Carwardine, Josie; Fensham, Rod J.; Butler, Don W.; Wilson, Kerrie A.; Possingham, Hugh P.; Martin, Tara G.
Highlights: Carbon farming can cost-effectively offset carbon emissions and deliver biodiversity co-benefits. The economics of two biodiversity-friendly carbon sequestration methodologies was analyzed. Assisted natural regeneration (ANR) was on average twice as profitable as environmental plantings. ANR can be an important carbon sequestration option in areas of intermediate levels of degradation. Abstract: Carbon farming in agricultural landscapes may provide a cost-effective mechanism for offsetting carbon emissions while delivering co-benefits for biodiversity through ecosystem restoration. Reforestation of landscapes using native tree and shrub species, termed environmental plantings, has been recognized as a carbon offset methodology which can contribute to biodiversity conservation as well as climate mitigation. However, far less attention has been paid to the potential for assisted natural regeneration in areas of low to intermediate levels of degradation, where regenerative capacity still remains and little intervention would be required to restore native vegetation. In this study, we considered the economics of carbon farming in the state of Queensland, Australia, where 30.6 million hectares of relatively recently deforested agricultural landscapes may be suitable for carbon farming. Using spatially explicit estimates of the rate of carbon sequestration and the opportunity cost of agricultural production, we used a discounted cash flow analysis to examine the economic viability of assisted natural regeneration relative to environmental plantings. We found that the average minimum carbon price required to make assisted natural regeneration viable was 60% lower than what was required to make environmental plantings viable ($65.8 t CO2 e −1 compared to $108.8 t CO2 e −1 ). Assisted natural regeneration could sequester 1.6 to 2.2 times the amount of carbon possible compared to environmental plantings alone over a range of hypothetical carbon prices and assuming a moderate 5% discount rate. Using a combination of methodologies, carbon farming was a viable land use in over 2.3% of our study extent with a low $5 t CO2 e −1 carbon price, and up to 10.5 million hectares (34%) with a carbon price of $50 t CO2 e −1 . Carbon sequestration supply and economic returns generated by assisted natural regeneration were relatively robust to variation in establishment costs and discount rates due to the utilization of low-cost techniques to reestablish native vegetation. Our study highlights the potential utility of assisted natural regeneration as a reforestation approach which can cost-effectively deliver both carbon and biodiversity benefits.